1996
DOI: 10.1108/eb020847
|View full text |Cite
|
Sign up to set email alerts
|

Clinical guidelines: involving patients and users of services

Abstract: National clinical guidelines can provide a way for health professionals, patients and users of services to work together to make decisions about care. For guidelines to have a positive impact on the quality of care, however, it is important that they are valid. The validity of a guideline is determined by its evidence base. Patients and users of services can contribute evidence about the quality of care and its outcomes which can be used to enhance a guideline's validity. Patient evidence can be accessed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Secondly, we found articles reflecting recommendations of committees or guideline developers on how to best develop and implement guidelines [ 6 , 16 , 26 , 44 , 50 ]. Two articles reflected on seminars that had been organised to discuss guideline development [ 14 , 20 ]. Then there were articles that referred to some publications but that could best be categorised as statements of opinion [ 3 , 36 , 39 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we found articles reflecting recommendations of committees or guideline developers on how to best develop and implement guidelines [ 6 , 16 , 26 , 44 , 50 ]. Two articles reflected on seminars that had been organised to discuss guideline development [ 14 , 20 ]. Then there were articles that referred to some publications but that could best be categorised as statements of opinion [ 3 , 36 , 39 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2003) [ 22 ] survey guideline development organizations ( n = 730) Gilmore (1993) [ 20 ] Duff et al. (1996) [ 14 ] Analysis of guidelines on among other things patient participation Opinion articles Burgers et al. (2004) [ 7 ] analyses of 100 guidelines in 13 countries Smolders and Braspenning (2005) [ 45 ] analysis of the Dutch depression guideline Bastian (1996) [ 3 ] Williamson (1998) [ 54 ] Saltman (1998) [ 39 ] Rogers (2002) [ 36 ] Studies of guideline development processes on among other things patient participation Model Eccles et al.…”
Section: Resultsmentioning
confidence: 99%
“…The ideological appeal seems to push the discussion into this direction. Regularly reference is made to Arnsteins ladder of participation; patients are not an equal partner yet and therefore should climb this ladder . In short, an important ideal is that more participation is better.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that unless guideline developers provide consumers participating in development groups with education and training, a clear explanation of their role, and sufficient support (e.g., more than one consumer representative), their involvement is likely to be tokenistic and relatively ineffective (313)(314)(315). In support, Tong et al (311) found that, when adequately assisted and engaged, consumers were able to contribute meaningfully to guideline development by identifying topics and outcomes (e.g., day-to-day management and overall illness experience) not identified by health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to engage consumers include involving consumers in guideline-development groups, providing drafts for feedback, conducting surveys of consumers or running consumer focus groups or workshops parallel to the clinical guideline development groups (308,(313)(314)(315). Some of these approaches have been criticised for being 'passive' or 'tokenistic' (314,315).…”
Section: Incorporating Patient Preferencesmentioning
confidence: 99%